Pengaruh Inovasi Produk Dan Kinerja Promosi Terhadap Keunggulan Bersaing Pada Sulaman Indah Mayang Di Kota Pariaman - ., Arivetullatif; Afrianti, Rini (CV. ITTC INDONESIA, 2024)
The aim of this research is to analyze the influence of product innovation and promotional performance on the competitive advantage of Mayang Indah Embroidery in Padang Birik-birik Village, Pariaman City simultaneously and partially. This research uses quantitative data, the data collected is in the form of values ​​or scores for the answers given by respondents to the statements in the questionnaire and processed using SPSS Version 16.0 for window. The sample was determined as 80 respondents using the purposive sampling method. The data analysis technique used is multiple linear regression analysis. Based on the research results, it is concluded: 1) Product Innovation has no effect on Competitive Advantage in Mayang Indah Embroidery in Padang Birik-birik Village, Pariaman City 2) Promotional Performance influences Competitive Advantage in Mayang Indah Embroidery in Padang Birik-birik Village, Pariaman City 3) Product Innovation and Promotional performance simultaneously influences Competitive Advantage in Mayang Indah Embroidery in Padang Birik-birik Village, Pariaman City with a significance level of 0.000<0.05. It can be concluded that innovation in Sulaman Mayang products does not have an impact on competitive advantage